2017
DOI: 10.1108/ijebr-10-2016-0337
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics between entrepreneurial orientation, transformational leadership, and intrapreneurial intention in Iranian R&D sector

Abstract: Purpose The purpose of this paper is to examine the relationship between entrepreneurial orientation (EO) and intrapreneurial intentions among knowledge workers in the Iranian R&D sector using transformational leadership (TL) as a moderator and to also investigate the extent of the knowledge workers’ intrapreneurial intentions. Design/methodology/approach The research was tested as a cross-sectional survey of knowledge workers involved in the R&D centers in Iran under the Society of the Centers for R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 135 publications
(195 reference statements)
0
39
0
2
Order By: Relevance
“…For instance, Maritz (2010) found that there is a significant relationship between networking with other research organizations and the level of entrepreneurship of a university. Razavi and Ab Aziz (2017) also indicated that networking, in addition to innovativeness, proactiveness and risk-taking, is an important factor in the intention to be intrapreneurial. Networking seems to be an important factor distinguishing intrapreneurs from entrepreneurs, in that intrapreneurs must act within an organization with a certain climate and political field (Smith et al 2016).…”
Section: Behaviormentioning
confidence: 99%
“…For instance, Maritz (2010) found that there is a significant relationship between networking with other research organizations and the level of entrepreneurship of a university. Razavi and Ab Aziz (2017) also indicated that networking, in addition to innovativeness, proactiveness and risk-taking, is an important factor in the intention to be intrapreneurial. Networking seems to be an important factor distinguishing intrapreneurs from entrepreneurs, in that intrapreneurs must act within an organization with a certain climate and political field (Smith et al 2016).…”
Section: Behaviormentioning
confidence: 99%
“…Time availability fosters entrepreneurial activity by proving employees with the necessary time to explore new ideas and to work on pet projects (Hornsby et al 2002). Finally, organizational boundaries should be flexible enough to stimulate information exchange between departments and with external partners, but certain enough to coordinate entrepreneurial behavior across the organization (Hornsby et al 2002;Bjornali and Støren 2012;Kuratko et al 2014;Razavi and Ab Aziz 2017).…”
Section: Corporate Entrepreneurshipmentioning
confidence: 99%
“…By leveraging innovation, risk, competitive aggressiveness and proactiveness, universities have been creating an increasing number of entrepreneurs (Clarysse and Moray, 2004; Martens et al, 2016; O’Shea et al, 2005; Razavi and Ab Aziz, 2017; Walter et al, 2006). Universities aim to spur the development of spin-offs to enhance innovation efficiency (Libaers and Wang, 2012) to improve the local economy (Marion et al, 2012; Mian, 1997).…”
Section: Eo and Spin-offmentioning
confidence: 99%